Social Corporatism and Capital Accumulation: The Fate of the Nordic Model - Jonathan Perraton (Intereconomics, 2018)
Recent research into weak productivity performance since the financial crisis has highlighted the importance of the gap between the most productive firms and the rest. While wage compression may only be one possible mechanism to promote the relative growth of productive firms, it does appear to be effective in promoting productivity growth in Nordic economies.
Keywords: 330